2009
DOI: 10.1029/2008wr007532
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of seabed mixing and intertidal zone discharge in coastal aquifers

Abstract: [1] Contaminant loading from an inland source zone to the nearshore marine environment is examined using a saturated-unsaturated simulation model which incorporates both the influence of the growth and the extinction of the seepage face in the intertidal zone and the inclusion of hydromechanical stress coupling due to tidal loading. The system analyzed represents a site where an unconfined aquifer extends offshore with a broad intertidal zone. The volumetric discharge of groundwater in the intertidal zone domi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…However, the total stress on the beach sediment is not constant and varies in the same way as the pore water pressure, thus giving an invariant effective stress (i.e., no expansion or contraction of sediment matrix). To account for the total stress variation and remove the artificial pressure wave, a tidal loading term needs to be incorporated into Richards' equation [ Reeves et al , 2000; Gardner and Wilson , 2006; Maji and Smith , 2009]. On the other hand, numerical tests [ Xin et al , 2009] showed that if the saturated hydraulic conductivity of sediments is larger than 10 −6 m/s, the compressibility plays a negligible role in governing the groundwater flow in the sediment.…”
Section: Mathematical Models and Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the total stress on the beach sediment is not constant and varies in the same way as the pore water pressure, thus giving an invariant effective stress (i.e., no expansion or contraction of sediment matrix). To account for the total stress variation and remove the artificial pressure wave, a tidal loading term needs to be incorporated into Richards' equation [ Reeves et al , 2000; Gardner and Wilson , 2006; Maji and Smith , 2009]. On the other hand, numerical tests [ Xin et al , 2009] showed that if the saturated hydraulic conductivity of sediments is larger than 10 −6 m/s, the compressibility plays a negligible role in governing the groundwater flow in the sediment.…”
Section: Mathematical Models and Simulationsmentioning
confidence: 99%
“…At most natural coasts, the subterranean estuary is also exposed to the influence of oceanic oscillations, including tides and waves. Tidal effects have been examined extensively in many recent studies based on numerical modeling [ Prieto and Destouni , 2005; Mao et al , 2006; Brovelli et al , 2007; Robinson et al , 2007a, 2007b; Robinson et al , 2009; Li et al , 2008; Maji and Smith , 2009; Li et al , 2009], field measurements [ Vandenbohede and Lebbe , 2005; Robinson et al , 2006] and laboratory experiments [ Boufadel , 2000; Robinson and Li , 2004; Colbert et al , 2008; Anschutz et al , 2009]. It has been revealed that tidal sea level oscillations induce relatively rapid recirculation of large amounts of seawater through the subterranean estuary, which contributes significantly to the SGD.…”
Section: Introductionmentioning
confidence: 99%
“…Intertidal groundwater flow is a component of SGD, occurring in a domain of transient and dynamic mixing of marine and terrestrial waters that has been described and referred to as a subterranean estuary (STE) [ Moore , ]. Intertidal porewater flow is induced both by tidal and wave action as well as by terrestrial hydraulic head gradients, creating a dynamic, spatially heterogeneous flow system [ McLachlan and Turner , ; Robinson et al ., ; Robinson et al ., ; Maji and Smith , ; Xin et al ., ]. While STE mixing occurs across a broad range of scales [ Bratton , ], the intertidal zone acts as both a transient upper boundary condition and outlet for the shallowest expression of the STE, producing dynamic environmental conditions in the foreshore forced by terrestrial and marine processes.…”
Section: Introductionmentioning
confidence: 99%
“…The FGD is typically most important for nitrate and for other contaminants originating on the upland watershed. The DSD is important for transport of nutrients mineralized in bottom sediments, and the ISD can transport metabolites of the shallow coastal aquifer [Brovelli et al, 2007;Maji and Smith, 2009;Robinson et al, 2009]. Furthermore, each of these fluxes carries different concentrations of environmental tracers, such as radium isotopes, that are measured in the coastal waters to quantify the groundwater discharge.…”
Section: Introductionmentioning
confidence: 99%